出生時体重および乳幼児期の運動発達と児童期の身体活動量との関係 - Aoyama, Tomoko; Tanaka, Shigeho; Tanaka, Maki; Okuda, Masayuki; Inoue, Shigeru; Tanaka, Chiaki (Hatsuiku hattatsu kenkyuu, 2017)
Low birth weight has been associated with lower levels of physical activity in later life as assessed by questionnaires. Earlier infant motor development was also recently shown to be an early predictor of physical activity as indicated by an increased frequency of sports participation during adolescence. The aim of the present study was to determine the associations between birth weight plus the timing of infant motor development and moderate to vigorous physical activity in children. The subjects were 379 elementary school children aged 6-12 years. The children's current weight and height were evaluated, and their birth weight and the age when the child first walked unassisted were reported based on their parent's memory. The children's physical activity was objectively measured using accelerometry（Active style Pro HJA-350IT, OMRON). The time（min／day）spent in moderate to vigorous physical activity（Metabolic equivalents［METs] ≥3）was derived from the accelerometry data. Our analyses revealed that the children's age at walking unassisted was inversely correlated with the time spent in moderate to vigorous physical activity（r＝ .0.24）when controlled for gender and current age. A multiple linear regression analysis revealed that later age at walking unassisted was significantly associated with decreased time spent in moderate to vigorous physical activity（B＝-2.28, p＜0.001), independent of gender, current age, body weight, and wearing time. There was no evidence of an association between birth weight and moderate to vigorous physical activity. The present findings indicate that delayed infant motor development, in terms of age at walking unassisted, may predict lower levels of physical activity in children. Appropriate interventions to prevent physical inactivity may be needed for infants with slower motor development.